Eye Tracking Trends in Chemistry Learning: Bibliometric Study 2018-2023 on Google Scholar with VOSviewer and Pivot Table - Muna, Khairiatul; Bahit, Muhammad (Journal of Innovative Science Education, 2023)
The development of research topics in the field of eye tracking has become a good trend at the international level because eye tracking is not only used in the fields of health or psychology but can also be used in education, including chemistry and science learning. This research aims to look at trends and updates on the topic of eye tracking in chemistry learning so that gaps and research opportunities can be found. This research uses bibliometric methods with articles collected from Google Scholar and VOSviewer software is used to analyze and visualize the relationship of various elements in the dataset. From the results of the analysis, information was obtained: (1) the development of eye tracking publications in the context of learning chemistry, science and pure chemistry experienced fluctuations in the publication timeframe 2018-2023; (2) the publisher that publishes a lot of eye-tracking literature is Elsavier; (3) United States is the country with the most authors; (4) the journal that receives the most eye-tracking articles is Computers & Education; (5) It is known that 83.5% of eye tracking articles are published in Q1-Q3 journals; (6) authors who have conducted a lot of research on the topic of eye tracking are "Sigfredo Fuentez, Claudia Gonzalez Viejo and Richard E. Mayer"; (7) There are 162 keywords divided into 19 clusters; ; (8) "eye movements, eye tracking and virtual reality" are keywords that appear frequently; (9) Eye tracking research topics in chemistry learning that are still little researched are "drawing, learning processes, stem content knowledge, visual spatial content, gaze tracking, visual problems, perceptual learning". This research also found trends as well as research gaps and opportunities related to the topic of eye tracking in chemistry, science and pure chemistry learning